International trauma life support for emergency care providers - Alson, Roy L.; Han, Kyee H.; Campbell, John E. (Pearson Education Limited, 2021)
International Trauma Life Support for Emergency Care Providers has been at the forefront of trauma education for all levels of prehospital emergency care worldwide. This complete resource is filled with practical, hands-on training that guides readers through the how's and the why's of all the skills needed for rapid assessment, resuscitation, stabilisation, and transportation of the trauma patient. The 9th edition reflects the latest and most effective approaches to prehospital trauma care, including a more functional approach to assessment and management.